CYSTOLITHIASIS WITH ASSOCIATED HYDRONEFROSIS IN A FEMALE PERSIAN CAT: A CASE REPORT - Valerie Xylia Tay; I Nyoman Suartha; Sri Kayati Widyastuti; I Wayan Nico Fajar Gunawan (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
This report describes the diagnosis and management of cystolithiasis in an 8-year-old, spayed female Persian cat weighing 2.85 kg. The patient presented with a history of dysuria and hematuria that began nine months post-ovariohysterectomy. The symptoms initially resolved but recurred with greater severity a few days prior to presentation. Diagnostic tests, including urinalysis and ultrasonography, revealed hyperechoic particles within the urinary bladder and calcium oxalate crystalluria. A diagnosis of calcium oxalate cystolithiasis was made. The owner opted for conservative management, which included a prescription urinary diet and a daily herbal supplement (Keji Beling®). Clinical signs, including dysuria, resolved within seven days of treatment. However, calcium oxalate crystalluria persisted on follow-up urinalysis. This case suggests that conservative management can resolve the clinical signs of cystolithiasis, but long-term dietary control remains essential to manage the underlying risk of crystal formation. The role of herbal therapy in managing this condition requires further investigation.